2023
DOI: 10.3389/fnagi.2023.1188967
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of delirium after non-cardiac surgery in the Chinese elderly population: a systematic review and meta-analysis

Abstract: BackgroundPOD places a heavy burden on the healthcare system as the number of elderly people undergoing surgery is increasing annually because of the aging population. As a large country with a severely aging population, China's elderly population has reached 267 million. There has been no summary analysis of the pooled incidence of POD in the elderly Chinese population.MethodsSystematic search databases included PubMed, Web of Science, EMBASE, Cochrane Library Databases, China Knowledge Resource Integrated Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The preliminary test in this study found that nine covariates were expected to enter the Logistic regression. The POD incidence was 15% [ 24 ]. And the loss of follow-up rate was assumed to be 20%.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary test in this study found that nine covariates were expected to enter the Logistic regression. The POD incidence was 15% [ 24 ]. And the loss of follow-up rate was assumed to be 20%.…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review, different rates of incidence for postoperative delirium were found for surgeries of different organs or systems, the lowest incidence was 10% with urologic surgeries, and 26% was the overall incidence rate [ 1 ]. The incidence of delirium after noncardiac surgical procedures was found to be 18.6% (95% CI: 16.4-20.8) among the elderly population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%